(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article presents the research of the phenomenon of pedagogical upbringing as a didactic problem. The authors define upbringing as the process of formation of basic structures of personality, and pedagogical upbringing – as the formally organized and curated pedagogical process aimed at formation of the basic structures of personality. This process is carried out through education and other activities appropriate to the modern education system. The defining characteristics of the pedagogical upbringing are its systematic nature and purposefulness. They are: the strengthening of children and adult communities in the classroom and outside, development of the democratic bases of the educational process, overcoming the negative consequences of authoritarian upbringing, improvement of professional pedagogical culture of educators. Theoretical studies and experiments allowed influencing the development of innovative processes in educational institutions, improving the system of education management in the Baku region, and expanding the interdepartmental cooperation in education. The used techniques are correlated with the goals and objectives of the study. It defines the principles and ways of integrating in a unified educational system, offers a theoretical didactic model of education and the formation of the culture based on the principles of democratization and humanization of all processes. The practical significance consists in the fact that the research results can be applied to activities of different types of French students and to become the basis for their development and improvement. They also may aid the strengthening of the teaching community through enhancing the professional culture of teachers and leaders of the education system.